SCHOOL BUSINESS MANAGEMENT COMPETENCIES FOR IMPROVED ADMINISTRATIVE EFFECTIVENESS IN PUBLIC SECONDARY SCHOOLS IN RIVERS STATE NIGERIA - Richard Anietie; Grace Phillips Ayonuwe (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2022)
The study investigated school business competencies for improved administrative effectiveness in Public Secondary School in Rivers State. Three research questions and two null hypotheses were formulated to guide the study. The population of the study was 286 principals in all the public secondary schools in Rivers State. A sample of 166 through a stratified random technique was determined using the Taro Yamane formula. The instrument of the study was a self design instrument captioned “School Business Management Competencies Questionnaire (SBMCQ) and Principal Administrative Effectiveness (PAE) with the reliability coefficients of 0.77 and 0.84 respectively which was determined through the Cronbach alpha statistics. Mean scores and standard deviation was used to answer the research questions while Pearson Product Moment Correlation Coefficient was sued to test the hypothesis. It was discovered that the highest kind of business available in the public school is related to cafeteria / canteen services and that also to a high extent, resourcefulness as a business management competency improves administrative effectiveness in public secondary schools in Rivers State. It concluded that for the school administrators to manage the school business effective (administrative effectiveness), they must possess the core competence of resourcefulness, conceptual thinking and administrative organisation. It was recommended among others that the principal should have a comprehensive understanding of the school complex nature and also think critically at both abstract and concrete level to harmonize a rather multifaceted business challenges in the school and proffer realistic solutions.